Caracterización de la vegetación alrededor de los senderos del sector Quebrada González, Parque Nacional Braulio Carrillo, Costa Rica. - Oviedo Pérez, Paúl E.; Alvarado Hernández, Abraham; Fournier Gutiérrez, Laura (Uniciencia, 2009)
We report the results of a preliminary analysis of the composition and structure of the forest growing near the paths of Quebrada González, Braulio Carrillo National Park, Costa Rica. Nine parcels of 20 x 20 m settled down subdivided in quadrants of 10 x 10 m. All trees with a diameter at breast height (DBH) of 10 cm or greater were marked, measured and identified. Two quadrants were selected by parcel and we recorded the number of individuals for species with a DBH smaller than 10 cm and a height greater than 50 cm. Also the amount of terrestrial large-leave plants was registered. A plastic tube was placed in the center of each parcel to estimate the density of the understory as the percentage of the longitude of the tube covered by the vegetation. A total of 143 trees were measured and 40 species were registered. The mean abundance and mean density was of 595,7 ± 155,5 individuals ha-1 and 266,3 ± 61,5 species ha-1 respectly. There was no significant difference in the forest composition when comparing the three study places (KW = 2, gl=2, p=0.9999). The species with highest Importance Value índex were Hedyosmum mexi-canum, Colubrina spinosa, Protium panamense and Vochysia spp. The diametric class distributions followed the expected J-invested shape. This forest has three well differentiated stories. The understory is very dense, dominated by Melastomataceae, Rubiaceae and terrestrial monocots. The middle-story measures among 10-20m and it is dominated by lasting successional species. The canopy rarely overpasses the 25, it is very discontinuous and it is dominated by Vochysia spp, Virola sebifera and Carapa guianensis. The results suggest that the forest of the Quebrada González is according to a premontane forest, with different periods of human disturbance and with an age between 25 and 35 years.